2023
DOI: 10.1007/s00167-023-07505-w
|View full text |Cite
|
Sign up to set email alerts
|

Long leg radiographs underestimate the degree of constitutional varus limb alignment and joint line obliquity in comparison with computed tomography: a radiographic study

Payam Tarassoli,
Luke E. Corban,
Jil A. Wood
et al.

Abstract: Purpose The purpose of this study was to understand if diferences exist between computed tomography (CT) and long leg radiographs (LLR) when deining coronal plane alignment of the lower limb in total knee arthroplasty (TKA). It aimed to identify any such diferences between the two imaging modalities by quantifying constitutional limb alignment (arithmetic hip-knee-ankle angle (aHKA), joint line obliquity (JLO) and Coronal Plane Alignment of the Knee (CPAK) type within the same population. Methods A retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…As they are descriptive integrators of alignment variables, we used the Functional Knee Phenotypes (FKP) and CPAK systems to classify our cohort, both of which have been validated by studies using CT imaging [40–42]. Our preoperative alignments are strikingly similar to these (Table 5), thereby strengthening the hypothesis that plain radiography may underestimate the degree of deformity and constitutional joint line obliquity, and that the variation of phenotypes that exists is much broader than previously considered [35, 41].…”
Section: Discussionmentioning
confidence: 59%
“…As they are descriptive integrators of alignment variables, we used the Functional Knee Phenotypes (FKP) and CPAK systems to classify our cohort, both of which have been validated by studies using CT imaging [40–42]. Our preoperative alignments are strikingly similar to these (Table 5), thereby strengthening the hypothesis that plain radiography may underestimate the degree of deformity and constitutional joint line obliquity, and that the variation of phenotypes that exists is much broader than previously considered [35, 41].…”
Section: Discussionmentioning
confidence: 59%
“…There are several available methods for identifying native coronal plane morphology, including generic cartilage wear assumptions, use of long leg radiographs, or methods based on advanced imaging [ 12 15 ]. Some of the methods based on CT or MRI use proprietary algorithms that may not be accessible to all surgeons [ 14 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our standard deviation was 3.4° with literature-based cartilage assumptions, which decreased to 3.1° with optimized cartilage assumptions. Tarassoli et al reported, in a subsequent study, that long leg radiographs underestimated proximal tibial varus in comparison to CT-based assessments by 1.3° on average [ 17 ]. The authors described that the MPTA, as measured from CT images, is sensitive to the sagittal position of the tibial landmarks [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All LSRs were taken with the patient barefooted, feet positioned to be shoulder width apart, and the knee in full extension. The patella was facing forward, and the hip and ankle joints were fully visible, which allowed the joint line measurement points to be clearly identified [27]. The x-ray tube was at 2 m perpendicular to the patient and was aimed at the centre of the knees.…”
Section: Radiological Analysismentioning
confidence: 99%